Development of Platform-Based Knowledge Map Service to get Data Insights of R&D Institution on User-Interested Subjects - Yang, MyungSeok; Joo, WonKyun; Choi, KiSeok; Kim, YoungKuk; Kim, YunJeong (Wireless personal communications, 2018)
Generally, any database is developed for the purpose of providing certain services for retrieval or management of data. If rules or processes designed to extract and analyze data in consideration of data characteristics are simplified and services are provided to users by visualizing analysis results in an easy-to-understand fashion, users will be able to get diverse insights easily without much cost or effort. If this kind of database is constructed and provided in NTIS database as well (e.g., project data, research outcome data such as paper and patent, personnel information, etc.) users might be able to get varied insights on national R&D data. The approach proposed in this study is significant in that it provides platform-based analysis services which can create a knowledge map after extracting and analyzing user-interested data and subsequently visualizing the results. Furthermore, this study is intended to make users obtain insight on a research institute more easily by providing analyzable additional information, not only as a list of research institutes in user-preferred subjects after providing the results of the analysis on R&D expenses, but also in regional distribution and annual changes in core research institutes, focusing on those taking part in national R&D programs in certain fields.